Effectiveness of exercise versus exercise plus tape in the manaqement of females with patellofemoral pain - Froehling, Lori A. (My University, 1996)
The difference among no treatment, use of traditional physical therapy exercises, and use of the same exercises plus patellar taping was investigated. Thirty female Ss (agesl8-43) with nontraumatic onset of knee pain of at least 6 week duration were assigned to an exercise, exercise plus tape, or control group. Ss in the exercise and exercise plus tape groups were instructed in flexibility and strengthening exercises which were progressed over 8 weeks. Ss in the exercise plus tape group also performed patellofemoral taping based on McConnell principles for 2 to 4 weeks. Data were gathered on subjective reporting of symptcms with the Hughston Sports Medicine Foundation, Inc.: Initial Knee History, symptom reproduction with performance of a functional activity, McConnell patellofernoral orientation, and surface electromyography of vastus medialis oblique (VMO) and vastus lateralis (VL) recruitment and ratio. The results indicated that Ss in the exercise plus tape group reported a significant decrease in subjective symptoms and progressed to painfree functional activities and improved VMO recruitment more quickly than subjects who used exercise alone, or those who received no treatment. The mechanism for this change was unclear but did not appear to be related to PF orientation or VM0:VL ratio which did not differ between groups or change over time.
Keywords: Sports accidents; Exercise for women - Physiological aspects; Patellofemoral joint